Tribunals (Scotland) Act 2014 : consultation on draft regulations regarding: (1) adding the Bus Lane Adjudicators to Schedule 1 of the Tribunals (Scotland) Act 2014; (2) the First -tier Tribunal for Scotland (Transfer of Functions and Members of the Parking and Bus Lane Adjudicators) to the Scottish Tribunals; (3) the First-tier Tribunal for Scotland General Regulatory Chamber Parking and Bus Lane Appeals (Procedure); (4) The First-tier Tribunal for Scotland General Regulatory Chamber Parking and Bus Lane Cases and Upper Tribunal for Scotland (Composition).: consultation on draft regulations regarding: (1) adding the Bus Lane Adjudicators to Schedule 1 of the Tribunals (Scotland) Act 2014; (2) the First -tier Tribunal for Scotland (Transfer of Functions and Members of the Parking and Bus Lane Adjudicators) to the Scottish Tribunals; (3) the First-tier Tribunal for Scotland General Regulatory Chamber Parking and Bus Lane Appeals (Procedure); (4) The First-tier Tribunal for Scotland General Regulatory Chamber Parking and Bus Lane Cases and Upper Tribunal for Scotland (Composition). (2018) - Unknown
No abstract available